Cost of illness of RSV infection in a middle-income tropical country - Buendía, Jefferson Antonio; Patino, Diana Guerrero; Sinisterra, Denis (The Turkish Journal of Pediatrics, 2021)
Background. Despite the burden of disease of Respiratory syncytial virus (RSV) infection in children, there are important gaps in knowledge about the potential impact in terms of health as well as social and healthcare resources. The aim of this study was to describe the economic burden of RSV in the first two years of life in Colombia. Methods. We conducted a cost-of-illness study, taking a population prevalence-based approach. A decision tree model was constructed with a time horizon of two years. We defined the following outcomes: death, RSV infection with long term complications, RSV with acute complications, RSV without complications. Inpatient and outpatient costs were collected directly from medical invoices of patients who attended a tertiary referral hospital. Results. The mean cost per patient with an RSV infection was US$ 178.35 CI 95% (30.7-541.67 US$). The total cost of RSV infection in children less than 2 years in Colombia was US $ 64 443 616 per year (CI 95% US$11 092 902 - US$195 722 867). In the probabilistic sensitivity analysis, the mean cost per patient with RSV infection was only sensitive to changes in the cost of recurrent wheezing, cost of outpatient visits and cost of hospitalizations. Conclusion. The infection by RSV in Colombia generates a high economic burden on the health system. Generating comprehensive data on healthcare resource use and costs associated with RSV will help to provide valuable information for the development of cost-effectiveness models, and help guide prevention strategies against RSV.
Keywords: Colombia; cost; respiratory syncytial virus